The Effectiveness of High-Intensity Interval Training on Cardiorespiratory Fitness: A Systematic Review - Azzahra, Faizah Aulia; Arifin, Safrin (Majalah Ilmiah Fisioterapi Indonesia, 2025)
Background : High-Intensity Interval Training (HIIT) is a time-efficient exercise modality shown to improve cardiorespiratory fitness (CRF), particularly among adolescents with overweight or obesity, populations at elevated risk for cardiometabolic disorders. HIIT, characterized by alternating short bursts of intense activity with recovery periods, has gained increasing attention in both educational and clinical contexts. This systematic review aimed to evaluate the effectiveness of HIIT in improving CRF among adolescents. Methods : This review followed PRISMA 2020 guidelines. Comprehensive searches were conducted across four databases (PubMed, Scopus, ScienceDirect, and Google Scholar) using the keywords: “High-Intensity Interval Training” OR “HIIT” AND “Cardiorespiratory Fitness” OR “Cardiorespiratory Fitness Measures.” Randomized controlled trials (RCTs) published between 2021 and 2025 in Scopus-indexed journals were included. Eligibility was determined using the PICOS framework: Participants—adolescents with overweight or obesity; Intervention—HIIT protocols; Comparators—standard care or alternative exercises; Outcomes—CRF measures such as VO?max; Study design—RCTs. Methodological quality was assessed using the PEDro Scale. A narrative synthesis was conducted due to heterogeneity in intervention protocols and outcome measures. Results : Of 84 records screened, 8 RCTs met the inclusion criteria. All studies reported significant improvements in CRF, particularly in VO?max, following HIIT interventions. Additionally, school-based HIIT programs positively influenced body composition, metabolic markers (e.g., insulin, fat), and psychological well-being. Conclusion : HIIT is an effective, practical, and scalable strategy for enhancing CRF in adolescents. Its adaptability and efficiency support broader implementation in school-based and preventive health programs. Future studies should aim to standardize protocols and explore long-term impacts. Keywords : high-intensity interval training, cardiorespiratory fitness, adolescents, VO?max, HIIT